Global Macroeconomic Repercussions of US Trade Restrictions : Evidence from a GVAR Model - Kempa, Bernd; Khan, Nazmus Sadat (Taylor and Francis, 2019)
We employ a global vector autoregression (GVAR) model to analyze international spillover effects of US trade restrictions, modeled as a reduction of US imports. Our sample consists of the US and 25 countries in the rest of the world, grouped into larger regions comprising European nations, non-European industrial countries and emerging economies. We find US trade restrictions to reduce trade volumes and income levels in the rest of the world as well as in the US. The trade balance deteriorates across all world regions except in the US, where it is unaffected by the trade restrictions. We also model the effects of a trade war in which the rest of the world responds in equal measure to the trade restrictions imposed by the US. We again find that export and import activity recedes both in the US and in the rest of the world, although the resulting effects are now strongest in the short run. The trade balance improves in the rest of the world but deteriorates in the US. In terms of the GDP response, the rest of the world is initially much harder hit by the imposition of the retaliatory trade measure than is the US.